Use of Limited Transthoracic Echocardiography in Patients With Traumatic Cardiac Arrest Decreases the Rate of Nontherapeutic Thoracotomy and Hospital Costs. (1st October 2014) - Ferrada, Paula; Wolfe, Luke; Anand, Rahul J.; Whelan, James; Vanguri, Poornima; Malhotra, Ajai; Goldberg, Stephanie; Duane, Therese; Aboutanos, Michel
Abstract : Objectives: Limited transthoracic echocardiography (LTTE) has been introduced as a hemodynamic tool for trauma patients. The aim of this study was to evaluate the utility of LTTE during the evaluation of nonsurviving patients who presented to the trauma bay with traumatic cardiac arrest. Methods: Approval by the Institutional Review Board was obtained. All nonsurviving patients with traumatic cardiac arrest who reached the trauma bay were evaluated retrospectively for 1 year. Comparisons between groups of patients in whom LTTE was performed as part of the resuscitation effort and those in whom it was not performed were conducted. Results: From January 2012 to January 2013, 37 patients did not survive traumatic cardiac arrest while in the trauma bay: 14 in the LTTE group and 23 in the non–LTTE group. When comparing the LTTE and non–LTTE groups, both were similar in sex distribution (LTTE, 86% male; non–LTTE, 74% male; P = .68), age (34.8 versus 24.1 years; P = .55), Injury Severity Score (41.0 versus 38.2; P = .48), and percentage of penetrating trauma (21.6% versus 21.7%; P = .29). Compared with the non–LTTE group, the LTTE group spent significantly less time in the trauma bay (13.7 versus 37.9 minutes; P = .01), received fewer blood products (7.1% versus 31.2%; P = .789), and were less likely to undergo nontherapeutic thoracotomy in the emergency department (7.14% versus 39.1%; P < .05). The non–LTTE group had a mean of $3040.50 in hospital costs, compared with the mean for the LTTE group of $1871.60 ( P = .0054). Conclusions: In this study, image‐guided resuscitation with LTTE decreased the time in the trauma bay and avoided nontherapeutic thoracotomy in nonsurviving trauma patients. Limited TTE could improve the use of health care resources in patients with traumatic cardiac arrest.